Association of dental neglect scale and severity of dental caries among nursing students: A cross-sectional study - S Athira; Chitra Girija Vallabhan; Sujith Sivarajan; C Dithi; P J Swathy Anand; Thara Chandran (Wolters Kluwer Medknow Publications, 2021)
Aims: The aim of this study is to assess the utilization of available dental services and home dental care practices in a sample of nursing students and to seek out the correlation if any, between the Dental Neglect Scale (DNS) scores and severity of dental caries. Subjects and Methods: The study was conducted among 630 nursing students aged 18-21 years from the area of South Bangalore. The study was cross-sectional in design and a convenience sampling method was adopted to get the desired sample size. A prestructured questionnaire was administered to the students in their classrooms. Following this, a brief oral examination was conducted using mouth mirror and light for the detection of any visible carious lesions. Results: The dental attendance variable was found to be significantly associated with the DNS scores (P < 0.001). The DNS scores were significantly higher (P < 0.001) among those who had visible caries than those who do not. A very good correlation was obtained between scores of DNS and the caries severity (P < 0.001, r = 0.773). Conclusions: The DNS can be a very good predictor of the dental attendance pattern as well as clinically assessed severity of carious lesions.